Closed-form solutions for predicting the thick elastic plate behavior of CLT and timber panels with gaps. (1st June 2018) - Franzoni, L.; Lebée, A.; Lyon, F.; Forêt, G.
Highlights: The elastic behavior of CLT and innovative timber panels with gaps is investigated. CLT and timber panels with gaps are modeled as a beam space frame. A thick-plate homogenization scheme is applied. Closed-form solutions predicting the elastic plate behavior are derived. The solutions are compared to existing simplified methods and FE results and gives good predictions. Abstract: In a former paper by the authors (Franzoni et al., 2017), the elastic behavior of Cross Laminated Timber (CLT) and timber panels having periodic gaps between lateral lamellae has been analyzed. A thick plate homogenization scheme based on Finite Elements computations has been applied. The predicted behavior was in agreement with experimental results. In this paper, simplified closed-form solutions are derived in order to avoid FE modeling. Both cases of narrow gaps of CLT panels and wide gaps of innovative lightweight panels are investigated. CLT and timber panels with gaps are modeled as a space frame of beams connected with wooden blocks. The contribution of both beams and blocks to the panel's mechanical response is taken into account, leading to closed-form expressions for predicting the panel's stiffnesses and maximum longitudinal and rolling shear stresses. The derived closed-form solutions are in agreement with the reference FE results and they can be used for practical design purposes.